How does immigration affect natives' task-specialisation? Evidence from the United Kingdom - Martina Bisello (University of Essex, Institute for Social and Economic Research (ISER), 2014)
In this paper we empirically test the predictions of Peri and Sparber (2009) model of comparative advantage in tasks performance to evaluate whether in the United Kingdom immigration affected the way natives specialise in the task they perform on the job. Using Labour Force Survey and UK Skills Survey data from 1997 through 2006, we find that less-educated natives responded to immigration inflows of similarly educated workers by increasing their supply of communication tasks, relative to manual tasks. We also show that this effect varies across demographic groups, being higher among men, young people and workers with primary education (or less).
Keywords: F22; J61; J24; 330; Immigration; Task Specialisation; United Kingdom